De-Politicizing Youth Suicide Prevention - Shahtahmasebi, Said (Frontiers in Pediatrics, 2013)
Despite a large volume of research literature on suicide, the approach to suicide prevention is still firmly based on a medical model. Recently, the Chief Coroner in New Zealand expressed the view that current techniques have failed to reduce the suicide rate and a new approach is needed. However, the call for a new approach is often interpreted as disparities in access to mental health services so resources are directed to increase public access to them. Current evidence suggests that persisting with depression and mental illness as a rationale for suicide prevention is unwise and is highly politicised. For example, over the last decade or so, despite a sustained awareness campaign on depression and mental illness and the doubling of prescriptions for anti-depressants, suicide rates maintained an increasing trend over the same period. It is argued that a new approach must redefine the suicide prevention problem holistically so that the whole community may share ownership of the problem. This paper argues that in order to move forward with a new approach, suicide prevention must be de-politicised – and describes a grassroots approach to de-politicisation. Initial results suggest that with the grassroots approach there is potential to save lives, and it is cost-effective and sustainable.